The Effect of Using Mind Mapping to Students’ Reading Comprehension - Gresti Fina Ramadhan; Endah Tri Wisudaningsih; Ririn Fatmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research was intended to analyze the effect of mind mapping towards students reading comprehension at twelfth grade in MAN 2 Probolinggo. A lot of students still struggle with reading. To overcome students' challenges, teachers should have tactics when teaching reading comprehension. Using two groups pre- and post-test at an experiment and a control group, this study used the quasi-experimental methodology. The sample classes, which included 17 students in each, were twelfth social 2 and twelfth social 3. Technique for data analysis utilizing the Paired Sample T Test. The alternative hypothesis is rejected if the significance value, or Sig (2-tailed), is more than 0.05. The hypothesis is accepted if the significance value, or Sig (2-tailed), is less than 0.05. According to the findings, students who learnt by using mind map were able to develop at a higher level. If the results of hypothesis testing indicate a Sig value (2-tailed) of 0.000 < 0.05, then the test decision-making methodology is appropriate. It can be inferred from paired Sample T Test that the mind map method affects students' capacity for reading comprehension